Gambaran Pelaksanaan Kegiatan Kelas Ibu Hamil Di Wilayah Kerja Puskesmas Mranggen Kabupaten Demak Description Of Implementation Of Pregnancy Class In Worked Area Of Public Health Centre Mranggen District Demak Regency - Rini Puspita Sari; Syamsulhuda Budi Mustofa; Kusyogo Cahyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Bacground: The high maternal mortality rate (MMR) and Infant Mortality Rate (IMR) in Indonesia related to pregnancy, childbirth, and postpartum so that one of promotive and preventive health ministry began intensively conducted the Pregnancy It’s means to learned together about pregnant women health form of face-to-face in groups. The purpose of this research to describe the implementation of pregnancy class in worked area of public health centre Mranggen district Demak regency. Method ; The research was conducted at Mranggen Public Health Centre and a qualitative research method depth interview. Midwives 15 key informants selected by purposive sampling. The validity of the data used by the source triagulasi methods that follow the activity of Pregnancy Pregnancy classes and midwife coordinator. Result ; The results showed the picture of the implementation of the implementation class of pregnant women in health centers Mranggen Demak is good enough it is seen from POAC (planning, organizing, actuating dan controling) the planning still exist that do not have a plan, with a fairly good organizing with the cooperation with relevant parties Viewed actualing between planning and execution is appropriate, whereas views control, in each level of each already have a person in charge, and full reporting and routine every month. Conclusions; Direct supervision of a midwife coordinator advised to not rely solely on the monthly report